1999
DOI: 10.1093/carcin/20.8.1485
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine, a cancer chemopreventive agent, causes oxidative damage to cellular and isolated DNA

Abstract: Although N-acetylcysteine is an antioxidant which has been expected to be a cancer chemopreventive agent, its safety and risk assessment have not been evaluated. N-acetylcysteine increased the amount of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG), a characteristic oxidative DNA lesion, in human leukemia cell line HL-60, whereas the amount of 8-oxodG in HP100, which is a hydrogen peroxide (H(2)O(2))-resistant cell line derived from HL-60, was not increased. To clarify the mechanism of cellular DNA damage, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 46 publications
2
50
0
1
Order By: Relevance
“…Similarly, it was reported, using a simplified in vitro model, that an antioxidant vitamin E (␣-tocopherol) can act as a potent oxidative DNA-damaging agent in the presence of Cu(II) (14). Virtually all putative chemopreventive antioxidants may have potential carcinogenicity (18,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was reported, using a simplified in vitro model, that an antioxidant vitamin E (␣-tocopherol) can act as a potent oxidative DNA-damaging agent in the presence of Cu(II) (14). Virtually all putative chemopreventive antioxidants may have potential carcinogenicity (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed prooxidant effects of vitamin E (13,14) and vitamin C (15)(16)(17) under certain circumstances. Other antioxidants such as N-acetylcysteine (18) and quercetin (19,20) can cause oxidative damage to cellular and isolated DNA. ␤-Carotene may also act as both an antioxidant and a prooxidant under various oxygen partial pressures (21)(22)(23).…”
mentioning
confidence: 99%
“…glutathione, which was an even more potent scavenger of free radicals than NAC itself [12]. On the other hand, NAC and other reducing agents were also shown to increase the oxidative DNA damages, depending on the experimental conditions, such as the presence or absence of transition metal ions [20,[33][34][35]. It was demonstrated that NAC treatment increased the extent of oxidative DNA damage when copper or iron ions were involved [18,20,36,37].…”
Section: The Effect Of N-acetyl-l L-cysteine On Dna Damagementioning
confidence: 99%
“…However, there are still considerable controversies regarding the antioxidant efficacy of NAC. Some published experimental results suggested that NAC could increase the oxidative damage to DNA [18][19][20]. For example, Devasagayam et al [21] found that the degradation of pBR322 by free radicals was enhanced by treatment with NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literatures have demonstrated that antioxidants can act as prooxidants under some circumstances [19]. It is found that b-carotene [20], vitamin E [21], quercetin [22], N-acetylcysteine [23] , and caffeic acid [24] can act as potent DNA damaging agents. Also, a potential clastogenic effect of known antioxidant compounds has been reported by others.…”
Section: Discussionmentioning
confidence: 99%